The New Ireland Social Pension : A Review of the New Ireland Social Pension and Implications for the Papua New Guinea National Social Pension - Sibley, Jonathan; Ivaschenko, Alex; Pagau, Kerry; Tanhchareun, Tom (World Bank, Washington, DC, 2015)
This report commences the review and documentation of the New Ireland Old Age and Disability Social Pension. The review has focused on the design and operation of the scheme, including the payment modality, and the effectiveness of coverage of both the old age pension and disability components. The economic and social impact of the pension on recipients’ wellbeing, the wellbeing of their households and their communities has not been reviewed in detail, although limited qualitative research through focus group discussions has been undertaken as part of the review. The second objective of the report has been to draw key lessons from the New Ireland experience with the implementation of the social pension, which may inform the implementation of the national social pension.